Effects of Corporate Social Responsibility on Customer Loyalty: The Case Study of Beverage Consumption in Vietnam (Global Journal of Management and Business Research, 2023)
The study aims to analyze the influence of corporate social responsibility CSR on customer loyalty to beverage products Although there have been many studies on the impact of CSR on customer loyalty there was limited concern on the beverage industry especially in Vietnam The data were collected by a survey on 287 consumers with differences in gender age education level income and frequency of product use data collection and quantitative processing using Structural Equation Modeling Research results show that implementing CSR positively affects customer loyalty Implementing CSR has a direct impact on customer satisfaction thereby enhancing trust and maintaining loyalty to the beverage business and its products This research contributes to the theoretical review on the indirect impact of CSR on loyalty with the intermediate role of customer satisfaction The results particularly suggest recommendations for businesses in the beverage industry that desire to improve customer satisfaction and loyalty through enhancing the CSR practices
Keywords: corporatesocial responsibility; customer satisfaction; customer loyalty; beveragebrand